Unusual Syncope due to Intravascular Leiomyomatosis With Intracardiac Extension: A Case Report and Focused Literature Review - Ricardo Bohorquez Rodriguez; Edgar Giovanny Rios Dueñas; Nicolas Rodriguez Medina; Jesus Andres Beltran España; Cristian Orlando Porras Bueno (Clinical Case Reports)
ABSTRACT Intravascular leiomyomatosis with intracardiac extension is a rare disease that could cause syncope as the first manifestation. It should be suspected mostly in women of middle age with a medical history of uterine leiomyoma. Physicians must perform a multimodal imaging strategy to accurately characterize the mass's extension and perform the best treatment.